PENGEMBANGAN MODEL EVALUASI BIMBINGAN DAN KONSELING BERBASIS CIPP DI SMP KOTA BANJARMASIN - Qasthalani, Qasthalani; Jarkawi, Jarkawi; Ridhani, Akhmad Rizkhi; Abidarda, Yulizar (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2019)
Evaluation is an important activity in management because evaluation of a program can be seen as exhausted. There are several facts in the field regarding Guidance and Counseling evaluation, namely the lack of BK teacher knowledge of the Guidance and Counseling evaluation model, BK teachers are more focused on evaluating the process and the results relating to students and counselors using the 2014 and 2016 Guidance and Counseling Guidance BK teachers who do not have Guidance and Counseling guidelines as a reference for evaluating Guidance and Counseling. The purpose of this study is to find out the factual conditions of Guidance and counseling evaluation, analyze the needs of BK teachers for CIPP based Guidance and Counseling model evaluation and produce CIPP based Guidance and Counseling based evaluation models. The research method used is Research and Development (R & D) carried out with 4 steps namely preliminary study, hypothetical model development, expert validation and model revision. The analysis technique used uses miles and huberman techniques. The results of the study, the BK teacher carried out Guidance and Counseling evaluations well but not yet maximally, the BK teacher needed a comprehensive evaluation model and CIPP based Guidance and Counseling model evaluations that had been validated by experts and practitioners. CIPP based guidance and counseling that has been validated by experts and practitioners.